BIRTHPLACE, CULTURE, SELF-ESTEEM AND INTIMATE PARTNER VIOLENCE AMONG COMMUNITY DWELLING HISPANIC WOMEN - Gonzalez-Guarda, Rosa M. (2013)
The purpose of this study was to explore variations in demographics, culture, self-esteem and intimate partner violence among Hispanic women according to birthplace, and to identify factors that are associated with these differences in intimate partner violence. Baseline data from a randomized control trial testing the efficacy of an HIV prevention program was used. Path analyses identified differences in intimate partner violence between Colombian women and women from other Central/South American. Self-esteem was the only factor that was associated with these differences. Interventions that address the unique needs of Hispanic women from different subgroups are needed.